Religious Studies route A religious, philosophical and ethical studies and Christianity, Buddhism, Hinduism and Sikhism - Clarke, Steve; White, Joy; Ridley, Amanda; Pawson, Ed; Owens, Chris (Dynamic learning, 2020)
Bring out the best in every student; enable them to develop in-depth subject knowledge with this accessible and engaging Student Book, created by subject specialists and covering the content your students need to know for the reformed specification in a single book. - Helps students of all abilities fulfil their potential and increase their understanding through clear, detailed explanations of the key content and concepts - Motivates students to build and cement their knowledge and skills using a range of imaginative, innovative activities that support learning and revision - Provides a variety of quotes from sources of authority that students can draw on to enhance their responses and extend their learning - Encourages students to make links between the world religions and philosophical and ethical issues so they develop a holistic view of religion in modern Britain - Prepares students for examination with a rich bank of exam-style questions, guidance on how to improve responses and student-friendly assessment criteria - Enables you to teach unfamiliar topics and systematic studies confidently with clear explanations of Christian, Buddhist, Hindu and Sikh beliefs and practices, verified by faith organisations.